infrastructure of life - Lidin, Konstantin (project baikal, 2021)
The infrastructure of the city accompanies a person at all stages of their biography, including death as an integral attribute of life. This section includes three articles, the authors of which appear in our journal for the first time. The articles discuss strong trends that usually escape the attention of architectural theorists. There is a return of communal and other forms of housing where people unrelated to each other live under the same roof. Is it a global trend or a forced measure against economic hardships? A rethink of the rental house, a rapid shift in the balance from home ownership to rental housing – how will this affect the architecture of cities?In the general trend of changing attitudes to death and the process of dying, the subject of hospice architecture until recently was taboo, but now strongly attracts architects’ attention. The articles of our new authors are more of a question-posing and problematic nature, which is exactly in the style of our journal.
Keywords: communal housing; rental house; hospice architecture